The Influence of Gender Values and Gender Roles on The Resilience of Fisherman Families During The Pandemic COVID-19: The Influence of Gender Values and Gender Roles on The Resilience of Fisherman Families During The Pandemic COVID-19 - Nainggolan, Elizabeth Risda Mutiara; Herien Puspitawati (Journal of Family Sciences, 2023)
Fishermen's families, as the dominant family in coastal regions, are inextricably linked to the COVID-19 pandemic effect. Each family member must adapt to the changes that occur due to the different factors that impact the lives of fishermen's families. This study was carried out in Eretan Wetan Village, Indramayu District. The study was worked out in April-May 2022. This research uses a non-probability sampling method and a purposive sampling technique. The data collected through interviews using a questionnaire was then processed with the help of Microsoft Office Excel 2013 software and the Statistical Package for Social Science (SPSS) 25.0 for Windows. This study's participants were fishermen's wives with at least one child. Multiple linear regression analysis indicate that gender values and gender roles significantly positively affect the resilience of fishing families. These results show that gender values and gender roles that work well are needed to maintain the resilience of fishing families, especially during the COVID-19 pandemic.